Effect of Coolant Nozzle Sizes on Turning Aluminum Alloy AL319 - Zainal Ariffin, Selamat; Nor Bahiyah, Baba; Mohd, Alias; A. R., Yusoff; M. M., Rahman (Informatics Publishing Limited, 2016)
Background/Objectives: The paper discusses about the optimum cutting parameters with combination of various sizes of nozzle coolant to optimize the surface roughness, chips deformation and dimensional accuracy in the turning process based on the selected setting parameters. The selected cutting parameters for this study were the cutting speed, feed rate, depth of cut and various diameters of nozzle coolant. Methods/Statistical Analysis: Experiments were conducted and investigated based on Design of Experiment (DOE) with Taguchi method. The research of the aggressive turning process on aluminum alloy (A319) for automotive applications is an effort to understand the high speed machining concept, which widely used in a variety of manufacturing industries especially in the automotive industry. Findings: The results show that the dominant failure mode is the surface roughness and dimensional accuracy when the nozzle orifice size increases during machining of the A319. The exploration for dimensional accuracy, productivity and the optimization of cutting speed in the technical and commercial aspects of the manufacturing processes of A319 are discussed in automotive components industries for further work. Applications/Improvements: The result of this study shows that the effectiveness and efficiency of the system can be identified and helps to solve potential problems.